Recognition and optimization of landscape genes in traditional settlements: a case of Meishan area - Xia, Huasha; Chen, Feihu (Journal of Environmental Engineering and Landscape Management, 2025)
Traditional settlement landscapes provide vital ecosystem services and represent significant cultural heritage, making their preservation crucial for national cultural development and rural revitalization. This study focuses on Meicheng Town in the Meishan area, utilizing landscape gene theory to classify and identify cultural landscape features. By integrating the Analytic Hierarchy Process (AHP) and Fuzzy Comprehensive Evaluation (FCE), the study develops a landscape gene sorting index system, systematically evaluating 16 sub-categories of landscape factors. The results highlight topography and building decoration as dominant features that should be prioritized for preservation. However, areas such as building materials, traditional culture, and folk customs require significant improvement. Additionally, the river and road landscapes present opportunities for enhancement to strengthen the town’s cultural identity and aesthetic quality. The study provides practical recommendations for optimizing Meicheng Town’s landscape, balancing the preservation of traditional elements with modern development needs. This approach addresses gaps in the literature on settlement landscape genes and offers strategies for sustainable rural cultural landscape development.